Pengaruh Kualitas Produk dan Green Marketing Terhadap Pembelian Ulang Dengan Kepuasan Konsumen Sebagai Variabel Intervening Pada Produk Skincare di Kota Semarang - Rahmi Yuliana; Setyo Pantawis (ECONBANK: Journal of Economics and Banking, 2022)
This study aims to determine the effect of product quality, green marketing on repeat purchases and intervening variables of consumer satisfaction. The population in this study are skincare consumers in the city of Semarang. Samples were taken as many as 100 respondents with accidental sampling method. The technique used in this research is Structural Equation Modeling (SEM) with Amos software. The results show that the effect of product quality has a positive and significant effect on consumer satisfaction, the positive and significant effect of green marketing on consumer satisfaction, the influence of consumer satisfaction has a positive and significant effect on repurchase, customer satisfaction mediates the effect of product quality on repurchase has a positive and significant effect. , customer satisfaction mediating the effect of green marking on repeat purchases proved to have a positive and significant effect.